The Role Of Instagram Social Media In Increasing Students Visit At The Library Of UIN Sunan Kalijaga Yogyakarta, Indonesia - Arina Faila Saufa (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Advances in information technology have had a great impact on libraries. Not only in terms of the progress of information systems but also a pattern of communication and information delivery. Instagram is one of the most popular social media for millennials. This is what makes the UIN Sunan Kalijaga library actively use Instagram as a more effective medium for conveying information. The purpose of this study was to determine the role of social media Instagram in increasing interest in visiting the UIN Sunan Kalijaga Yogyakarta library. The researcher uses a descriptive qualitative approach to explain the role of social media Instagram in increasing the interest of visiting users by analyzing posts on Instagram. The results show that the Instagram social media of the UIN Sunan Kalijaga library has several roles and objectives, namely 1) to inform, 2) to persuade, 3) to influence, 4) to educate, and 5) to entertain. From the results of the analysis, it can be concluded that social media Instagram provides many roles for libraries to encourage interest in visiting users and utilizing library services.